ANALISIS PERAN HASIL HUTAN BUKAN KAYU TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT KAMPUNG PESAYAN, KABUPATEN BERAU, KALIMANTAN TIMUR - RIZKI GUNAWAN (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
Forests provide significant economic value for communities living around them, particularly through non-timber forest products (NTFPs) such as honey, fruits, resin, and medicinal plants, which can be harvested sustainably without cutting down trees. In Kampung Pesayan, Berau Regency, East Kalimantan, local communities rely heavily on NTFPs, especially stingless bee (kelulut) honey, as a supplementary source of household income. This study aims to analyze the role of non-timber forest products in increasing community income in Kampung Pesayan. A quantitative approach was employed using a simple linear regression method, with data collected through questionnaires distributed to 47 NTFP farmers selected using a saturated sampling technique. The results show a regression equation of Y = 6.799 + 0.443X, indicating a positive relationship between NTFP utilization and community income. The t-test results reveal a t-count value of 2.911, greater than the t-table value of 2.014, with a significance value of 0.006, smaller than 0.05. These findings confirm that non-timber forest products have a positive and significant partial effect on increasing community income in Kampung Pesayan. Kelulut honey, in particular, contributes approximately 30–50% of total household income while also supporting forest sustainability through environmentally friendly harvesting practices. The study concludes that NTFPs serve as both an economic livelihood strategy and a conservation instrument for the community, and recommends farmer capacity building, institutional strengthening, market development, ecosystem protection, and government support to optimize the long-term contribution of NTFPs to community welfare and forest sustainability.